Kegiatan Pengabdian Masyarakat : Deteksi Dini Gangguan Metabolik dengan Pemeriksaan Parameter Trigliserida di Yayasan Baptis Cengkareng - Alfred Sutrisno Sim; Alexander Halim Santoso; Farell Christian Gunaidi; Eric Hartono; Dianova Soeltanong; Frilliesa Averina (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Triglyceride level examination is a crucial step in early detection of metabolic disorders. High triglyceride levels often occur without symptoms, but play a direct role in triggering dyslipidemia, insulin resistance, and increased cardiovascular risk. The implementation of the activity uses the Plan-Do-Check-Act (PDCA) approach. The examination was carried out directly using the Point-of-Care Testing (POCT) tool to assess triglyceride levels from blood samples. A total of 62 participants took the examination. A total of 46.8% of participants had high triglyceride levels, while 53.2% were still within normal limits. The highest triglyceride value reached 446.0 mg/dL and the median was 133.5 mg/dL. The majority of participants were female. Triglyceride examination identified participants with impaired lipid profiles. Education about physical activity needs to be part of a preventive strategy to lower triglyceride levels and reduce the risk of metabolic complications. Movement-based interventions can increase awareness and encourage healthier behavioral changes.